Role of beta-catenin in the developing cortical and hippocampal neuroepithelium - Machon, O; van den Bout, C J; Backman, M; Kemler, R; Krauss, S (Neuroscience, 2003)
beta-Catenin plays a pivotal role in Wnt signaling during embryogenesis and is a component of adherens junctions. Since targeted disruption of the beta-catenin gene is lethal at gastrulation we have used a D6-Cre mouse line for conditional inactivation of beta-catenin in the mouse cerebral cortex and hippocampus after embryonic day (E) 10.5. In D6-Cre floxed beta-catenin mice, hippocampal CA1-CA2 fields are disrupted in similar manner as in Wnt-3a and LEF-1 mutants. The cortex of D6-Cre floxed beta-catenin mutants is strongly affected which contrasts with the normal cortex observed in Wnt-3a and LEF-1 mutants. Severe abnormalities in the organization of the neuroepithelium are observed that include disrupted interkinetic nuclear migration, loss of adherens junctions, impaired radial migration of neurons toward superficial layers and decreased cell proliferation after E15.5. At newborn stage, a premature disassembly of the radial glial scaffold and increased numbers of astrocytes are found in the cortex.
Keywords: hybridizace in situ; beta Catenin; Cytoskeletal Proteins; mozková kůra; Mitosis; In Situ Hybridization; imunohistochemie; DNA vazebné proteiny; cytoskeletální proteiny; neurony; hipokampus; Cell Movement; Hippocampus; trans-aktivátory; Animals; Transcription Factors; myši transgenní; transkripční faktory; Immunohistochemistry; zvířata; Neurons; pohyb buněk; myši inbrední C57BL; Mice, Transgenic; myši; neuroglie; Trans-Activators; Mice, Inbred C57BL; Neuroglia; mitóza; Mice; DNA-Binding Proteins; beta-katenin; Cerebral Cortex